2013
DOI: 10.3390/pathogens2030506
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reduces Amyloid Fibrillation of Prion Protein and Decreases Reactive Oxidative Stress

Abstract: Misfolding and aggregation into amyloids of the prion protein (PrP) is responsible for the development of fatal transmissible neurodegenerative diseases. Various studies on curcumin demonstrate promise for the prevention of Alzheimer’s disease and inhibition of PrPres accumulation. To evaluate the effect of curcumin on amyloid fibrillation of prion protein, we first investigated the effect of curcumin on mouse prion protein (mPrP) in a cell-free system. Curcumin reduced the prion fibril formation significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Curcumin effectively rescues the cells from apoptosis and decreases the ROS level caused by subsequent co-incubation with prion amyloid fibrils. The assays in cell-free mPrP and in N2a cells of this work verified the promising effect of curcumin on the prevention of transmissible neurodegenerative diseases [107]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasesupporting
confidence: 58%
See 1 more Smart Citation
“…Curcumin effectively rescues the cells from apoptosis and decreases the ROS level caused by subsequent co-incubation with prion amyloid fibrils. The assays in cell-free mPrP and in N2a cells of this work verified the promising effect of curcumin on the prevention of transmissible neurodegenerative diseases [107]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasesupporting
confidence: 58%
“…Lin and colleagues (2013) [107] evaluated the effect of curcumin on amyloid fibrillation of prion protein on mouse prion protein (mPrP) in a cell-free system. Curcumin reduced the prion fibril formation significantly.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Earlier we have also shown that the curcumin rescues the protein from aggregation by increasing the reconfiguration rate [15]. Moreover, many researchers using a diverse group of peptides and proteins have demonstrated that curcumin inhibits fibril formation through one or other mechanisms [11,[14][15][16][17][18][19][20]. These studies form a very strong basis for the inhibitor hypothesis of curcumin.…”
Section: Introductionmentioning
confidence: 78%
“…These results indicated that F isomers preincubated with curcumin acquired a state which is more susceptible to aggregation than the N isomer. Curcumin, the main polyphenolic compound found in the spice turmeric, has been shown to inhibit fibrillar aggregation of different types of protein and peptides [14][15][16][17][18][19][20]. Recently, two independent works on the effect of curcumin on the amyloid fibril formation showed that curcumin promoted amyloid fibril formation by binding to oligomeric species of intrinsically disordered proteins (IDPs) [21,22].…”
Section: Effect Of Curcumin On the Unfolding And Stability Of Hsa Isomentioning
confidence: 99%
“…Curcumin selectively binds to, inhibits the aggregation of, and disassembles non-native, disease-related PrP isoforms [179]. It protects scrapie-infected neuroblastoma (scNB) [180] and murine neuroblastoma (N2a) cells [181] from the accumulation of neurotoxic PrP aggregates.…”
Section: Interfering With (Neuro)toxic Tau Species In the Aggregationmentioning
confidence: 99%